Deligate’s role and impact in the food system - Hoegberg, Chelsea; Olsson, Amanda (2021)
Food waste is occurring at all stages of the food supply chain and leading to environmental, economic, and social costs and injustices. While some actors are responsible for greater degrees of waste, every actor is being called upon to take action. The retail sector is one potential leverage point for reduction measures, but there currently exists insufficient data capturing abilities to fully track and resolve the inefficiencies leading to retail food waste. Upon recognizing this problem, the Swedish start-up company Deligate has created a program for retailers to track the best before dates of their inventory and take action before food expires, primarily by price reducing expiring items. Additionally, with a pilot self-service price reduction station, called Datum-Rabatten, Deligate is seeking to engage consumers in the issue of retail food waste. This paper set out to define the role Deligate is playing in the food system, what environmental impact the resulting potential reduction in food waste amounts to and finally to understand what factors may influence a consumer’s likeliness to engage with the self-service price reduction station. Utilizing the concept of circularity brokerage as a means to close gaps in the food system leading to waste, Deligate’s role has shown to be critical in tackling avoidable retail food waste. Most importantly, Deligate is providing tools for measuring and monitoring grocery store inventories in addition to modifying existing retailer consumer relationships. Data including the top price reduced expiring items was extracted from Deligate’s program, categorized based on past environmental impact studies and the carbon footprint was calculated. It was shown that an average retailer can reduce its annual carbon footprint attributable to food waste by 4 641 kgCO2eq if they sell 100% of price reduced items. This study contributes to the growing body of food waste research by providing an estimation tool in the form of scenarios of sold price reduced food, which retailers can use to create or gauge alignment with food waste reduction goals. Trends in price reduced items also revealed key product categories which should be targeted and researched for re-evaluation, potentially involving retailers, other upstream actors and academia. In an effort to investigate consumer motivation to try Datum-Rabatten, an online survey was conducted to uncover consumer awareness, attitudes and shopping habits in regards to retail food waste. The results, framed in the Extended Theory of Planned Behavior, revealed that the main driver for trying Datum-Rabatten was economic incentive, followed by desire to prevent food waste. Despite feeling external pressure to personally act on the issue of food waste, results indicated that consumers view retail food waste as the retailers’ burden. The awareness of retail food waste and living environment showed very little effect on willingness to try Datum-Rabatten. Overall, respondents were receptive to the concept, indicating some willingness to accept a role in reducing retail food waste. The results of this study are intended to be used in the further development of Datum-Rabatten and other future initiatives to reduce retail food waste. May this thesis serve as an example of how external actors can join the food system, create novel connections to resolve inefficiencies and create a more robust and sustainable food system for the future.